The Blue Shield Initiative. Joining Efforts to Preserve our Cultural Heritage in Danger - Varlamoff, Marie-Thérèse (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
Each year dramatic and unexpected events erase part of our memory by destroying the documentary heritage that has been accumulated in our libraries, archives or museums. Two world wars, as well as unavoidable and recurrent disasters, have added to the already extensive list of documents that have vanished for ever. A list of libraries and archives that have been totally or partially destroyed has been compiled and published in 1996 by IFLA and ICA in the framework of the UNESCO „Memory of the World Programme” . It is appalling. The recent and dramatic events in Kosovo, East Timor or Sierra Leone, to quote just a few, testify the dangers threatening cultural heritage in the event of armed conflicts. Natural disasters like floods, fires, hurricanes or landslides do not unfortunately lack behind. Generally the danger seems very far away but you must always keep in mind that this can happen to you as well and the best way to respond is to be prepared and get ready. My concern today is to explain how institutions like libraries, archives and museums have decided to join to mitigate the consequences when a disaster strikes. This is why they created the „ International Committee of the Blue Shield” (ICBS).